2012
DOI: 10.1002/ijc.27902
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of calcium sensing receptor null cells: A highly malignant and drug resistant phenotype of colon cancer

Abstract: The effects of elastomer type on the morphology, flammability, and mechanical properties of high‐impact polystyrene (HIPS)/polystyrene (PS)‐encapsulated magnesium hydroxide (MH) were investigated. The ternary composites were characterized by cone calorimetry, mechanical testing, and scanning electron microscopy. Morphology was controlled with poly[styrene‐b‐(ethylene‐co‐butylene)‐b‐styrene] (SEBS) triblock copolymer or the corresponding maleinated poly[styrene‐b‐(ethylene‐co‐butylene)‐b‐styrene] (SEBS‐g‐MA). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 48 publications
0
54
1
Order By: Relevance
“…We hypothesize that a dynamic process of cell death and revival occurs in a culture and that CaSR null cells divide asymmetrically to replenish themselves and also differentiate into CaSR positive cells which will eventually apoptose and die. The expression profile of stem cell markers and survival markers in CaSR null cells lend support to this hypothesis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We hypothesize that a dynamic process of cell death and revival occurs in a culture and that CaSR null cells divide asymmetrically to replenish themselves and also differentiate into CaSR positive cells which will eventually apoptose and die. The expression profile of stem cell markers and survival markers in CaSR null cells lend support to this hypothesis.…”
Section: Discussionmentioning
confidence: 66%
“…β‐actin was used as loading controls. As shown, untreated CaSR null cells do not express CaSR . The level of protein expression in cells treated with vitamin D or Aquamin was compared to that of the Ca 2+ treated cells with an assigned value of 1.0…”
Section: Resultsmentioning
confidence: 99%
“…Using miRNA array and real-time PCR, Wang et al20 found that the expression level of miR-135b was significantly upregulated in colonic cancer tissues compared with paracancerous tissues. Singh et al21 reported that the overexpression of miR-135b was associated with the reduction of tumor suppressive E-cadherin expression in colon carcinoma cell lines. Munding et al22 identified miR-135b as one of the new miRNA biomarkers for pancreatic ductal adenocarcinoma in human pancreas acinar and ductal cells by using miRNA array and real-time PCR, which has improved early diagnosis modalities and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have shown that knockdown of km23-1 inhibited the cell migration and invasion of human CRC cells, implicating km23-1 in the motility of invasive human CRC cells. The CRC cell models employed in our studies have KRAS (or BRAF) mutations [24], [45] and/or activated epidermal growth factor receptor (EGFR) pathways [58] , but they express comparatively low levels of EMT markers (ie, Snail1/2, Twist, and FOXC2 [59]), and their morphological features are indicative of an epithelial nature [59]. Along these lines, while colon cancer is generally considered to be a molecularly heterogeneous disease, two primary intrinsic subtypes that predict disease progression and recurrence have been identified [29].…”
Section: Discussionmentioning
confidence: 99%